Changes in anxiety and depression over 2 years in medically stable patients after myocardial infarction and their spouses in the Home Automatic External Defibrillator Trial (HAT): a longitudinal observational study. Issue 5 (7th October 2010) - Thomas, Sue A; Friedmann, Erika; Lee, Hyeon-Joo; Son, Heesook; Morton, Patricia G; ,
Abstract : Objective: To compare the long-term effects of cardiopulmonary resuscitation (CPR) training and CPR/automatic external defibrillator (AED) training on anxiety and depression of patients who were medically stable after myocardial infarction (MI) and of their spouses/companions. Design: Longitudinal. Participants: Post-MI patients (N=460) and their spouses/companions from the Home Automatic External Defibrillator Trial. Main outcome measures: Depression (Beck Depression Inventory-II scores) and anxiety (State Trait Anxiety Inventory scores). Results: At study entry, 25% of the patients and 15% of their spouses were depressed and 21% of the patients and 19% of the spouses were anxious. The prevalence of depression and anxiety did not change over time in the patients or their spouses. Average depression and anxiety decreased for patients but not for spouses. An intervention group did not contribute significantly to these changes. Psychological distress, indicated by depression or anxiety of the spouse or the patient, occurred in 191 couples. Among psychologically distressed patients (N=128), depression and anxiety decreased over time; the intervention group did not contribute to these changes. The reduction in anxiety among male patients was greater than in female patients (p=0.012, 95% CI 0.002 to 0.018). Among psychologically distressed spouses (N=118), depression decreased over time independently of the intervention. Changes in spouse anxiety depended on the intervention group (p=0.012, 95% CI 0.001 to 0.012); anxiety decreased significantly in the CPR and remained high in the CPR/AED group. Conclusion: There was no evidence that home AEDs caused psychological distress among patients. Even among those who were psychologically distressed when they were assigned to receive either CPR training or CPR/AEDs, home AEDs did not influence changes in patients' depression or anxiety or spouses' depression in comparison with CPR training. Among psychologically distressed spouses, AEDs may keep anxiety higher than it would be otherwise. Interventions to reduce anxiety of spouses who are psychologically distressed may be indicated when their partners receive an AED.